Social Listening as a Marketing Strategy to Analyze Beyond Consumer Buyology in the OTT Industry : A Research Note - Khatri, Sonal; Kale, Shailendrakumar (Prabandhan: Indian Journal of Management, 2022)
The burgeoning vogue of over the top (OTT) media in India has amplified the competition in the Indian entertainment industry, trying its best to win over the viewers by understanding their buyology. However, capturing the sentiments and expectations attached with rapidly changing entertainment choices and preferences of the OTT viewers is beyond understanding consumer buyology. Literary sources highlighted that there are various studies on social media catering to distinct perspectives. However, studies focusing on social listening in the OTT industry’s context are limited. Hence, there is a void in the ideologies and theoretical contribution on social listening concerning the OTT industry. This research note, perhaps formulated for massive research on social media in OTT, attempted to introduce the 4Rs of social listening such as, reach & enquire; relate & evolve; respond & engage; and relationship building & emotional connect.